Any Given Sunday: How Season Ticket Holders' Time of Stadium Entrance Is Influenced by Outcome Uncertainty - Dominik Schreyer; Sascha L. Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2013)
This paper constitutes a unique micro-level exploration of the relation between game outcome uncertainty and the behavior of highly committed season ticket holders of a major Bundesliga soccer team. Specifically, we look at 3,113 season ticket holders attending all 17 home games in the 2012-13 season and explore whether outcome uncertainty had an impact on their stadium arrival time. We find strong evidence that increased uncertainty about the expected outcome prompts these spectators to enter the stadium earlier. Moreover, season ticket holders travelling from outside the hosting city or paying higher season ticket prices exhibit a stronger reaction to uncertainty compared with season ticket hold ers in the standing section. We also find that younger spectators are less likely to arrive late when uncertainty increases.
Keywords: L83; D12; R22; Z19; 330; outcome uncertainty; soccer; football; consumer demand; attendance; season ticket holders